BUSINESS FEASIBILITY STUDY ANALYSIS OF THE FRUSTASHIT STORE BUSINESS IN TERMS OF NON-FINANCIAL ASPECTS AND FINANCIAL ASPECTS - Melani, Syeila; Elisah, Elisah; Maharani, Sofia; Devy, Jagad Kusuma; Widodasih, RR. Wening Ken (Universitas Muhammadiyah Tangerang, 2024)
This study aims to determine the business feasibility of the Frustashit Store business in terms of non-financial aspects through legal aspects and market and marketing aspects and financial aspects, namely financial aspects through the criteria for using the calculation of the results of the Payback Period, Net Present Value, Internal Rate of Return and Profitability Index. This research was analyzed using qualitative methods with a form of field research. The results showed that Frustashit Store MSMEs from the legal aspect were declared still not feasible because they had not completed the license letters, the market and marketing aspects were feasible because the products were of quality, affordable prices, wide distribution coverage and promotions carried out were attractive and from the results of the financial aspects were declared feasible because the acquisition of a positive NPV value> 0 of Rp 493,790,500, IRR value> interest rate of 16%, Payback Period (PP) obtained < investment life, namely 3 months 2 weeks, and Profability Index (PI)> 1, namely 3.66%.